Biomolecular Prospecting, Informative Gaps, and the Cancer Clinic: A Qualitative Fieldwork and an Epistemological, Historical and Ethical Analysis of Informed Consent for Clinical Trials for Monoclonal Antibodies and Biobank Research - D’Abramo, Flavio; Bont, Annemieke; Nüßlein, Lisa (Frontiers in Genetics, 2022)
What happens to cancer patients engaged in biomedical research when intellectual property regimes and ethical regimes intersect? This empirical qualitative study addresses this question by situating the experiences, hopes, and reasons of patients to enter clinical trials within the historical trajectory of informed consent and monoclonal antibodies, the biotechnology underpinning many targeted drugs used in oncological clinical trials and biobank research. Based on fieldwork we undertook in a German university hospital where we interviewed patients and the medical personnel, a historical review, and an ethical analysis we inquire into the effects that financial, legal, and technological reforms connected to the relevant pharmaceutical research and commerce have on cancer patients engaged in clinical trials and biobank research. We find that the controversial aspects of monoclonal antibodies, especially those related to the commercial interests at stake, enter the informed consent process mainly in the form of informative gaps. We highlight how a qualitative analysis of the clinic, especially when it is situated against the backdrop of the history of related technologies advancements and patent regime, it can serve the purpose of giving voice to subjects who are silenced by regimes of an ethical, epistemic, and commercial kind.